2019
DOI: 10.3390/agronomy9050218
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Callus and Cell Suspension Cultures of Selected Sorghum bicolor (L.) Moench Varieties: A Resource for Gene Discovery in Plant Stress Biology

Abstract: Sorghum, a naturally drought tolerant crop, is genetically diverse and provides a wide gene pool for exploitation in crop breeding. In this study, we experimentally assessed friable callus induction rates of seven sorghum varieties using shoot explant for the generation of cell suspension cultures. The cell suspensions were characterized in terms of cell growth and viability profiles as well as gene expression following 400 mM sorbitol-induced osmotic stress for 72 h. Only ICSB 338, a drought susceptible varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
2
13
0
3
Order By: Relevance
“…ICSB338 sorghum ( Sorghum bicolor ) cell suspension cultures initiated from shoot derived, dark-grown callus [ 36 ] were used in this study. Although the heat phenotypic trait of ICSB338 is currently unknown, this sorghum variety is relatively more susceptible to salt [ 37 ] and drought [ 38 ] stresses compared to other sorghum varieties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICSB338 sorghum ( Sorghum bicolor ) cell suspension cultures initiated from shoot derived, dark-grown callus [ 36 ] were used in this study. Although the heat phenotypic trait of ICSB338 is currently unknown, this sorghum variety is relatively more susceptible to salt [ 37 ] and drought [ 38 ] stresses compared to other sorghum varieties.…”
Section: Methodsmentioning
confidence: 99%
“…Cell cultures were grown and maintained under continuous darkness with agitation at 27 °C (±2 °C) every 10–12 days and sub-cultured for at least three generations prior to stress treatments. Eight-day old ICSB338 sorghum cell suspension culture, growing at mid-log phase [ 36 ] were used for the heat stress experiments. Triplicate 50 mL cell culture samples each for the control and heat stress treatments were generated.…”
Section: Methodsmentioning
confidence: 99%
“…Seleksi kalus remah juga dilakukan pada SE karet terutama pada jalur long-term SE (Cailloux et al, 1996), kalus ini juga digunakan sebagai bahan penyimpanan kalus jangka panjang dengan kriopreservasi (Lardet et al, 2007). Seleksi kalus juga dilakukan pada kultur suspensi Artemisia Annua L. (Jin & Keng, 2013), Boerhaavia paniculata Rich (Souza et al, 2014), Manihot esculenta Crantz (Apio et al, 2015), Grewia tenax (Dafalla et al, 2019), Sorghum bicolor L. (Ramulifho et al, 2019). Kalus remah memiliki Kalus primer stevia berupa kalus dengan struktur lunak berwarna bening atau translusen.…”
Section: Proliferasi Dan Seleksi Kalusunclassified
“…Also, it really depends on the level of endogenous auxin, both in the growth regulator organic plus liquitermy fertilizer and the organic pesticides my-1. The study of [26] showed that the callus process was highly dependent on explants and the addition of growth regulators to in vitro basic media. Based on the results of the coefficient of diversity test, the best porang embryogenic callus explants were seen in PortLT 3 (2ppm) because they were not significantly different from PortLT 2 (1ppm) and others.…”
Section: Porang Seed Embryogenic Callus Inductionmentioning
confidence: 99%